2023
DOI: 10.1021/acs.jpca.2c08967
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Impact of Helium Tagging on Flexible Molecules: Probing Microsolvation Effects of Protonated Acetylene by Quantum Configurational Entropy

Abstract: Helium, the lightest and most weakly interacting noble gas, is well-known for its unsurpassed chemical inertness. In many applications of helium in experimental techniques, such as tagging, messenger, or nanodroplet isolation action spectroscopy of molecules or complexes, it is assumed that the interaction of helium with the respective species, and thus the resulting interaction-induced perturbation, is small enough not to affect their structure and dynamics. Here, we probe the impact of one up to many attache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The most probable structure of a molecule is uniquely defined by the global maximum of the (diagonal of the) many‐body nuclear density matrix in its full dimensionality, which is certainly independent from any choice of embedding but difficult to visualize for polyatomics. Thus, one can successively unfold the computed many‐body ND by determining the most probable structure in a series of subspaces [10,30] . Starting with the HHe2+ ${{\rm{HHe}}_2^ + }$ core, the most probable structure is the perfectly collinear arrangement within that subspace of HHe3+ ${{\rm{HHe}}_3^ + }$ .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most probable structure of a molecule is uniquely defined by the global maximum of the (diagonal of the) many‐body nuclear density matrix in its full dimensionality, which is certainly independent from any choice of embedding but difficult to visualize for polyatomics. Thus, one can successively unfold the computed many‐body ND by determining the most probable structure in a series of subspaces [10,30] . Starting with the HHe2+ ${{\rm{HHe}}_2^ + }$ core, the most probable structure is the perfectly collinear arrangement within that subspace of HHe3+ ${{\rm{HHe}}_3^ + }$ .…”
Section: Resultsmentioning
confidence: 99%
“…Thus, one can successively unfold the computed many-body ND by determining the most probable structure in a series of subspaces. [10,30] Starting with the HHe þ 2 core, the most probable structure is the perfectly collinear arrangement within that subspace of HHe þ 3 . The most probable location of the third He atom, however, does not turn out to be a point according to our ND analysis, but is given instead by a circular line around the central proton that yields the most probable structure of HHe þ 3 .…”
Section: Resultsmentioning
confidence: 99%
“…76 Recently, Marx et al have used internal coordinates bond lengths and azimuthal and polar angle to describe the conformation of a fluxional molecule (protonated acetylene) and used the kNN method to assess its entropy. 79,80 The authors in particular assessed the two-, three-, and four-variable correlation using interaction information, expressed in terms of n-variable entropies, similar to the MIE expansion. 81 Hnizdo et al reported first the application of the kNN method for estimating the configurational entropy 82 of molecules, using only torsional degrees of freedom.…”
Section: Conformational Entropymentioning
confidence: 99%